“Análisis a la gestión financiera para la toma de decisiones de la Asociación de Producción Agrícola de Cacao Nacional La Maná “Asoprocanam” período 2017-2018”. - Pérez Mosquera, Milena Beatriz (2020)
The research had as a general objective to determine a diagnosis of financial management for the corresponding decision making in La Maná Association of Agricultural Production of National Cocoa “ASOPROCANAM” in the period 2017-2018. The Association has a lack of knowledge in the area of financial management, although it has managed to position itself in the market, the financial management is making a lot of mistakes that have led it to face serious problems, such as the embezzlement of money, it does not have a well-defined planning and does not have absolute control over income and expenses. That is why it has focused on carrying out an analysis to know the current weaknesses to present a proposal for improvement that is the guide, helping to improve the decisions in the functional and commercial processes of the activities that they carry out daily. This project seeks to strengthen the financial area and the decision-making of the association so it can keep a more efficient control of its records of activities both buying and selling cocoa, to encourage costs, expenses and investments and to determine what the profitability is, perform a good financial management research demand of the analytical-inductive method, with a quantitative approach to study the impact that an adequate financial management achieves.